Feasibility and cost of using mobile phones for capturing drug safety information in peri-urban settlement in Ghana: a prospective cohort study of patients with uncomplicated malaria. (December 2015) - Kukula, Vida; Dodoo, Alexander; Akpakli, Jonas; Narh-Bana, Solomon; Clerk, Christine; Adjei, Alexander; Awini, Elizabeth; Manye, Simon; Nagai, Richard; Odonkor, Gabriel; Nikoi, Christian; Adjuik, Martin; et al.
Abstract Background The growing need to capture data on health and health events using faster and efficient means to enable prompt evidence-based decision-making is making the use of mobile phones for health an alternative means to capture anti-malarial drug safety data. This paper examined the feasibility and cost of using mobile phones vis-à-vis home visit to monitor adverse events (AEs) related to artemisinin-based combination therapy (ACT) for treatment of uncomplicated malaria in peri-urban Ghana. Methods A prospective, observational, cohort study conducted on 4270 patients prescribed ACT in 21 health facilities. The patients were actively followed by telephone or home visit to document AEs associated with anti-malarial drugs. Call duration and travel distances of each visit were recorded. Pre-paid call cards and fuel for motorbike travels were used to determine cost of conducting both follow-ups. Ms-Excel 2010 and STATA 11.2 were used for analysis. Results Of the 4270 patients recruited, 4124 (96.6 %) were successfully followed up and analyzed. Of these, 1126/4124 (27.3 %) were children under 5 years. Most 3790/4124 (91.9 %) follow-ups were done within 7 days of ACT intake. Overall, follow up by phone (2671/4124—64.8 %) was almost two times the number done by home visits (1453/4124—35.2 %). Duration of telephone calls ranged from 38 s to 53 min, costing between GH¢0.26 (0.20USD) and GH¢41.70 (27.USD). On the average, the calls lasted 3 min 51 s (SD = 3 min, 21 s) costing GH¢2.70 (0.77USD). Distance travelled for home visit ranged from 0.65 to 62 km costing GH¢0.29 (0.20USD) and GH¢279.00 (79.70USD). Thirty-two per cent (1128/4124) of patients reported AEs. In total, 1831 AE were reported, 1016/1831(55.5 %) by telephone and 815/1831 (44.5 %) by home visits. Events such as nausea, dizziness, diarrhoea, and vomiting were commonly reported. Conclusion Majority of patients was successfully followed up by telephone and reported the most AEs. The cost of telephone interviewing was almost two times less than the cost of home visit. Telephone follow up should be considered for monitoring drug adverse events in low resource settings.